IMPLEMENTASI NILAI-NILAI KARAKTER DAN NORMA SOSIOMATEMATIK DALAM PEMBELAJARAN MATEMATIKA - Rahma Siska Utari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Characteristics of a nation are reflected in its people. Character values need to be implemented by society in everyday life because with characteristic that match with personality of nation, make us become civilized nation. Education is a way to instill the values of character to some people, especially learners who are the next generation of the nation. In each subject, character values can be applied, not least in math learning. Moreover, the planting of this character value is a government program that is illustrated and implemented in the curriculum used in Indonesia today. Implementation of character values in the process of learning mathematics can bring socio mathematical norms in it. Thus, the values of characters or characteristics that are formed not only within the learners (individual) but also formed from their social interaction obtained in the process of learning mathematics.